2018
DOI: 10.3389/fendo.2018.00314
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemokines in Thyroid Cancer Microenvironment: Is CXCL8 the Main Player?

Abstract: Tumor-related inflammation does influence the biological behavior of neoplastic cells and ultimately the patient’s outcome. With specific regard to thyroid cancer, the issue of tumor-associated inflammation has been extensively studied and recently reviewed. However, the role of chemokines, which play a crucial role in determining the immuno-phenotype of tumor-related inflammation, was not addressed in previous reviews on the topic. Experimental evidence shows that thyroid cancer cells actively secrete a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 151 publications
(185 reference statements)
3
54
0
Order By: Relevance
“…We found that IL-32β overexpression in TPC-1 cells resulted in slightly less cell death, and a significant increase in IL-8 mRNA expression, whereas IL-32γ did not. IL-8 is an important pro-survival cytokine [26] and restoring the IL-8 signalling pathway has been found to rescue IL-32β-induced cell death in HEK293 cells [18]. Our results further showed that the expression of Ki-67, an important marker of proliferation, was slightly reduced after exogenous IL-32γ overexpression, suggesting a reduced proliferation potential.…”
Section: Discussionsupporting
confidence: 68%
“…We found that IL-32β overexpression in TPC-1 cells resulted in slightly less cell death, and a significant increase in IL-8 mRNA expression, whereas IL-32γ did not. IL-8 is an important pro-survival cytokine [26] and restoring the IL-8 signalling pathway has been found to rescue IL-32β-induced cell death in HEK293 cells [18]. Our results further showed that the expression of Ki-67, an important marker of proliferation, was slightly reduced after exogenous IL-32γ overexpression, suggesting a reduced proliferation potential.…”
Section: Discussionsupporting
confidence: 68%
“…CXCR2 binds the CXCL1, CXCL2, CXCL3, CXCL5, CXCL6, CXCL7 and CXCL8 chemokines. Among them, CXCL8 plays a major role in thyroid cancer microenvironment (Rotondi et al 2007(Rotondi et al , 2018. CXCR2 was described originally in leukocytes and subsequently in non-hematopoietic cells, such as keratinocytes, neurons and epidermal cells, in regions corresponding to intermediate levels of differentiation (Baggiolini et al 1989, Tecimer et al 2000, Waugh & Wilson 2008.…”
Section: Cxcr1 and Cxcr2mentioning
confidence: 99%
“…The mechanisms involved in the effect of CXCR7 on tumor progression were studied by Zhang et al who showed that CXCR7 regulates growth and metastasis of PTC cells via the activation of the PI3K/AKT pathway and its downstream NF-κB signaling, as well as via the downregulation of cell differentiation, by downregulating Notch signaling (Zhang et al 2015). Furthermore, Zhang et al (2016) recently reported that a high expression of CXCR7 increases both CXCL8 and VEGF levels, two main molecules with proven pro-tumorigenic effect (Rotondi et al 2018).…”
Section: Cxcr7mentioning
confidence: 99%
“…Moreover, doxorubicin time-and dose-dependently enhanced CCL20 expression in SKOV3 cells. The aberrant expressions of chemokines were often found in various tumors (Gao and Fish, 2018;Karin, 2018;Rotondi et al, 2018;Zhao et al, 2018). CCL20 belongs to CC chemokine family and plays key roles in the development of different kinds of cancers.…”
Section: Discussionmentioning
confidence: 99%